ŞEKİL HATIRLAMALI POLİMER KARIŞIMLARIN ÜRETİLMESİ VE TERMAL ÖZELLİKLERİNİN İNCELENMESİ - CHERKEZOVA, AYBOLEK (Fırat Üniveristesi, 2022)
Bu tez çalışmasında, PEG, PLA şekil hatırlamalı polimerleri ve PVC kullanılarak PVC-PEG ve PEG-PLA iki farklı tip değişik oranlarda polimer karışımlar elde edilmiştir. Elde edilen bu karışımların, FTIR ile fonksiyonel grup analizleri yapıldı ve herbir polimerin sahip olduğu karakteristik özelliği gösterdiği tespit edilmiştir. Alınan DSC ölçümlerinden, heriki polimer karışımının içindeki polimerlerin erime piklerinin görüldüğü tespit edildi. Bu da bize bu karışımların karışabilir özellik sergilediğini gösterir. Polimer karışımların Termogravimetrik ölçüm cihazı ile termal stabilitesi belirlendi. Polimer karışım oranına göre termal stabilitenin değiştiği tespit edilmiştir. Kristallik özellik gösteren, PLA ve PEG polimerlerinin bulunduğu polimer karışımlarının kristallik dereceleri oda sıcaklığında alınan x-ışınları ölçümleri ile belirlendi.

In this thesis, two different types of PVC-PEG and PEG-PLA polymer blend with different ratios were obtained by using PEG, PLA shape memory polymers and PVC polymers. Functional group analyzes of these mixtures were performed with FTIR and it was determined that each polymer showed its characteristic properties. From the DSC measurements taken, it was determined that the melting peaks of the polymers in both polymer blends were observed. This shows us that these blends exhibit immissible properties. The thermal stability of the polymer blends was determined with a Thermogravimetric measuring device. It has been determined that the thermal stability changes according to the polymer mixing ratio. The crystallinity of the polymer blends containing PLA and PEG polymers with crystalline properties were determined by x-ray measurements taken at room temperature.
Production of shape memory polymer blends and investigation of their thermal properties
Keywords: Fizik ve Fizik Mühendisliği